2019
DOI: 10.3390/coatings9020112
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Laboratory Bioassay for Evaluating the Efficacy of Antifouling Paints on Amphibalanus amphitrite Using a Flow-Through System

Abstract: With the aim of establishing a protocol for evaluating the efficacy of antifouling paints on different organisms, a flow-through laboratory test using triangular boxes was developed for cyprids of the barnacle Amphibalanus (=Balanus) amphitrite. Six different formulations of antifouling paints were prepared in increasing content (0 to 40 wt.%) of Cu2O, which is the most commonly used antifouling substance, and each formulation of paint was coated on one surface of each test plate. The test plates were aged for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…This method is novel in that it evaluates the behavior of barnacles inside a triangular box in a flow-through system to determine how well antifouling paints inhibit barnacle growth. This study also demonstrated a highly reliable way for antifouling agent efficacy evaluation [247]. Antunes et al (2019) designed a multi-bioassay approach that efficiently assessed the potential antifouling activities of cyanobacterium Phormidium sp.…”
Section: Implementation Of Novel Antifouling Bioassays To Overcome Th...mentioning
confidence: 98%
“…This method is novel in that it evaluates the behavior of barnacles inside a triangular box in a flow-through system to determine how well antifouling paints inhibit barnacle growth. This study also demonstrated a highly reliable way for antifouling agent efficacy evaluation [247]. Antunes et al (2019) designed a multi-bioassay approach that efficiently assessed the potential antifouling activities of cyanobacterium Phormidium sp.…”
Section: Implementation Of Novel Antifouling Bioassays To Overcome Th...mentioning
confidence: 98%
“…The testing was referred from the other reports. [19][20][21][22] The characteristics of the LF200 nanocomposite coating was assessed versus immersion time with the experiment duration of 60 days.…”
Section: Marine Antifouling Laboratory Testingmentioning
confidence: 99%
“…These two preparations were seen to reduce the complications related to hernia infection during surgery. Another study by Kojima et al investigated antifouling paints and developed a laboratory scale bioassay using a flow-through system [4]. They prepared antifouling biocide-releasing Cu 2 O-based paints for the inhibition of Amphibalanus amphitrite adhesion to a home-made container.…”
mentioning
confidence: 99%